Case Study of Diabetic Nephropathy Management by Combination Therapy including RAS blocker, DPP-4 Inhibitor and Pentoxifylline - Kang, Ran-Hui; Ri, Mi-Rae; Kong, Yong–Ju; Yu, Kang; O, Guang-Chun (Medical Science Journal for Advance Research, 2025)
Background: We introduce two cases of progressive diabetic nephropathy that were successfully managed with combination therapy including RAS blocker(Losartan), DPP-4 inhibitor(Linagliptin), pentoxifyllin. In case 1(Diabetes History 12 years, female, age 50 years, eGFR: 62.38mL/min/1.73m2, proteinuria:3.3g/d), her eGFR and proteinuria deteriorated(eGFR: 50.54mL/min/1.73m2, proteinuria:4.3 g/d, annual eGFR change: -17.76mL/min/1.73m2) after 8 months using of amlodipine and atenolol as BP control agents, we replaced them with losartan and pentoxifylline and could observe some improvement in eGFR change (annual eGFR change: -11.46mL/min/1.73m2) with slight reduction in proteinuria(3.7g/d). Therefore, we added linagliptin which finally led to significant improvement both in eGFR(55.65 mL/min/1.73m2) and proteinuria(2.5g/d). In case 2(Dibetes History 10 years, male, age 64 years, eGFR: 59.07 mL/min/1.73m2, proteinuria: 2.9g/d), he had controled his blood pressure with amlopdine and atenolol but his protienuria and eGFR did worsend after 1 year (eGFR:49.92 mL/min/1.73m2, proteinruia: 3.6g/d), therefore we replaced amlodipine and atenolol with losartan and added linagliptin for renoprotective and glycemic control measure but there was no significant improvement in eGFR(44.58 mL/min/1.73m2) so we added pentoxifylline which finally led to improvement in eGFR(53.89 mL/min/1.73m2).